2018
DOI: 10.1080/17435390.2018.1472312
|View full text |Cite
|
Sign up to set email alerts
|

Nanofibrillated cellulose causes acute pulmonary inflammation that subsides within a month

Abstract: Nanofibrillated cellulose (NFC) is a renewable nanomaterial that has beneficial uses in various applications such as packaging materials and paper. Like carbon nanotubes (CNT), NFCs have high aspect ratio and favorable mechanical properties. The aspect ratio also rises a concern whether NFC could pose a health risk and induce pathologies, similar to those triggered by multi-walled CNT. In this study, we explored the immunomodulatory properties of four NFCs in vitro and in vivo, and compared the results with da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 46 publications
7
55
1
Order By: Relevance
“…To date, twelve studies from 2011–2018 have been published on the short-term inhalation toxicity of CNs [12,13,14,15,16,17,18,19,20,21,22,23]. These studies use both cellular (in vitro) [16,17,18,19,20,21] and animal (in vivo) [12,13,14,15,16,22,23] models to investigate the effect of CNC and CNF exposure on the lung. The main findings from these studies are summarized here before analyzing the studies using two published approaches for their usefulness for risk assessment purposes.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…To date, twelve studies from 2011–2018 have been published on the short-term inhalation toxicity of CNs [12,13,14,15,16,17,18,19,20,21,22,23]. These studies use both cellular (in vitro) [16,17,18,19,20,21] and animal (in vivo) [12,13,14,15,16,22,23] models to investigate the effect of CNC and CNF exposure on the lung. The main findings from these studies are summarized here before analyzing the studies using two published approaches for their usefulness for risk assessment purposes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A similarly designed study by Ilves et al (2018) examined the cytotoxicity and pro-inflammatory cytokine production in THP-1 cells following exposure to four surface-modified CNFs and compared these responses to conventional cellulose [16]. The authors found that one of the unmodified CNFs reduced cell viability and triggered pro-inflammatory cytokine production; the remaining three CNF materials had no significant changes and were similar to the response observed for bulk-sized cellulose.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the results of toxicity studies of metal nanomaterials, we consider that the research on the toxicity of CNs should be carried out urgently. Till now, the toxicity of these biomass CNs were reported mainly in the inhalation toxicity to the lung in both cellular [20][21][22] and animal [20,23,24] models. These investigations demonstrated CN exposures resulted in in ammatory responses [19].…”
Section: Introductionmentioning
confidence: 99%